Магнитное поле проводников и их поверхностный эффект - Китаев, Александр Васильевич (НТУ "ХПИ", 2010)
In present work the results of experimental investigations of the magnetic field pattern inside wires, between wires, and outside the two-wire line. It was defined that the current flowing in the wires does not produce magnetic field inside the wires. Magnetic field between and outside the wires dynamically changes depending on the current magnitude and geometric dimensions used. In the paper was shown that under conditions of objective reality the phenomenon of skin effect is not present in accepted definition of this term due to a lack of the magnetic field and irregular current distribution through the cross section of a conductor. However the term «skin effect» can be kept in educational and technical literature but its physical meaning have to be changed, for instance, into the phenomena of forming of a magnetic field in a conductor by a current, flowing on conductor surface etc.
The magnetic field of conductors and their skin effect
Keywords: ток электрический; сердечник; пластина алюминиевая; контур обгоревшего масла; индукция магнитная; кабель коаксиальный